2017
DOI: 10.1182/blood-2017-01-763219
|View full text |Cite|
|
Sign up to set email alerts
|

Robust patient-derived xenografts of MDS/MPN overlap syndromes capture the unique characteristics of CMML and JMML

Abstract: • Genetically accurate xenografts of CMML are achievable with near 100% frequency in NSGS mice.• Robust human engraftment and overt phenotypes of CMML and JMML xenografts here facilitate preclinical therapeutic evaluation in vivo.Chronic myelomonocytic leukemia (CMML) and juvenile myelomonocytic leukemia (JMML) are myelodysplastic syndrome (MDS)/myeloproliferative neoplasm (MPN) overlap disorders characterized by monocytosis, myelodysplasia, and a characteristic hypersensitivity to granulocyte-macrophage colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 50 publications
2
84
0
Order By: Relevance
“…Consequently, the CMML PDX mouse model is vital to understanding CMML pathogenesis and to developing improved therapeutic approaches. 31 Metrics indicative of effective human CMML PDX engraftment of NSGS mice include thrombocytopenia, splenomegaly, the presence of CMML infi ltrates in histopathologic sections of murine organs, and the presence of CD45 + cells in FACS-analyzed isolates of murine spleen, bone marrow, and peripheral blood. All of these CMML model metrics were signifi cantly decreased in the C. bovis PCRpositive cohort that we describe here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, the CMML PDX mouse model is vital to understanding CMML pathogenesis and to developing improved therapeutic approaches. 31 Metrics indicative of effective human CMML PDX engraftment of NSGS mice include thrombocytopenia, splenomegaly, the presence of CMML infi ltrates in histopathologic sections of murine organs, and the presence of CD45 + cells in FACS-analyzed isolates of murine spleen, bone marrow, and peripheral blood. All of these CMML model metrics were signifi cantly decreased in the C. bovis PCRpositive cohort that we describe here.…”
Section: Discussionmentioning
confidence: 99%
“…30 In our prior report of this CMML mouse model, we demonstrated that sublethally irradiated NSGS mice are engrafted by CMML primary PDX as purified CD34 + cells, unfractionated bone marrow, or PBMC, resulting in splenomegaly, thrombocytopenia, and immunohistochemically localizable CMML infiltrates in the bone marrow, spleen, liver, and lung of engrafted NSGS mice and thus recapitulating the human condition. 31 This CMML PDX mouse model was found to be genetically and phenotypically accurate, with serially transplanted PDX cells in NSGS mice remaining similar to the original immunophenotype, morphology, and genetic mutations of the CMML patient. 31 This new mouse model permits the characterization of CMML disease pathogenesis and the testing of novel CMML therapeutics but is limited by the rarity of CMML patient specimens for NSGS mouse engraftment.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…These morphologically, immunophenotypically, and genetically accurate models will pave the way for in vivo biological studies and preclinical testing of novel therapies. 1 …”
mentioning
confidence: 99%